50‐Fold EQE Improvement up to 6.27% of Solution‐Processed All‐Inorganic Perovskite CsPbBr3 QLEDs via Surface Ligand Density Control. Issue 5 (24th November 2016) - Li, Jianhai; Xu, Leimeng; Wang, Tao; Song, Jizhong; Chen, Jiawei; Xue, Jie; Dong, Yuhui; Cai, Bo; Shan, Qingsong; Han, Boning; Zeng, Haibo
Abstract : Solution‐processed CsPbBr3 quantum‐dot light‐emitting diodes with a 50‐fold external quantum efficiency improvement (up to 6.27%) are achieved through balancing surface passivation and carrier injection via ligand density control (treating with hexane/ethyl acetate mixed solvent), which induces the coexistence of high levels of ink stability, photoluminescence quantum yields, thin‐film uniformity, and carrier‐injection efficiency.